PENINGKATAN PERFORMA BISNIS MELALUI MANAJEMEN PEMBERDAYAAN KARYAWAN PADA USP KUD MINATANI BRONDONG - Wulandari, Ayu; Suyitno, Suyitno; Azizi, Alvin Nur; Ulyah, Resa Maghfiratul; Fitriniati, Yurika (Universitas Muhammadiyah Metro Lampung, 2023)
This study aims to determine the improvement of business performance through employee empowerment management at USP KUD Minatani Brondong using qualitative descriptive research methods. Data collection techniques include direct observation and interviews at USP KUD Minatani Brondong. USP KUD Minatani Brondong has successfully implemented the empowerment model of desire, trust, confidence, accountability and communication in helping to improve the business performance of KUD Minatani from various aspects. This is proven to be able to encourage employee motivation and improve employee performance. Improving employee performance as a result of the empowerment program provides good progress towards improving business performance at USP KUD Minatani, both the value of profitability and effectiveness and efficiency of production as well as customer satisfaction.